Hak Istri Sah atas Nafkah Pasca Poligami dalam Perspektif Perlindungan Hukum - Astri Yulisti Datau; Mutia Cherawaty Thalib; Julisa Aprilia Kaluku (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This research discusses the wife's right to support after polygamy from the perspective of legal protection. Marriage is a sacred thing that gives rise to rights and obligations for husband and wife, one of which is the husband's obligation to provide support for his wife. However, in practice, there are still cases where the legal wife does not receive support from her husband after the husband commits polygamy. This shows that there are problems in fulfilling the wife's right to support after polygamy. This research aims to analyze the legal protection of legal wives' rights to support after polygamy. The research method used is an empirical method with a statutory and case approach, and uses observation and interview data collection techniques. The research results show that legal protection for legal wives' rights to support after polygamy is inadequate, both in the Marriage Law and the Compilation of Islamic Law.